Peran Moderasi Kualitas Laporan Keuangan dalam Hubungan Kinerja Keuangan Daerah dan Belanja Modal - Purwati, Yuliana Eka; Firmansyah , Amrie (Politeknik Ganesha Medan, 2024)
Capital expenditures are budget expenditures for acquiring fixed assets and other assets that provide benefits for more than one accounting period. This study examines the influence of regional independence, PAD effectiveness, and regional dependence on capital expenditure, with financial reports' quality as a moderating variable. The study uses 15 financial statements of district/city governments in Lampung Province from 2013 to 2022. The sample used in this research was 148 observation data. The analysis technique used is multiple linear regression analysis for panel data. This study indicates that regional independence and PAD effectiveness do not affect capital expenditure. Regional dependence positively affects capital expenditure. The quality of financial reports can moderate the influence of regional dependence on capital expenditure. This study has practical contributions that can be used by the Ministry of Home Affairs and Regional Government to improve policies in allocating capital expenditure budgets in the regions.